Changes of the ST segment of foetal electrocardiogram and their correlations with the level of aspartate aminotransferase, alanine aminotransferase in diabetic pregnant women more than 30 years of age - Kubiak-Fortecka, Agnieszka; Wilczyński, Jan (Menopause Review/Przegląd Menopauzalny, 2010)
New technical and technological possibilities, which have recently appeared, led to an increase in the interest in the foetal electrocardiography. Thanks to the construction of special electrodes, the method of direct electrocardiography was implemented into general use in the intrapartum supervision of the condition of the foetus. The analysis of the direct foetal electrocardiograms may turn out to be a more precise diagnostic method with a greater prediction value than cardiotocography when it comes to the condition of the foetus and the newborn. Many works indicate an increase in the importance of the supervision by combining both methods. The aim of this study was to analyse changes of the ST segment of the foetal electrocardiogram (FECG) monitored using STAN®S21 and their correlations with levels of aspartate aminotransferase and alanine aminotransferase. We also analysed AST, ALT correlation with the pH value. We had 54 patients divided into three groups. Group one included 54 diabetic patients at the age of 30-34. Group two comprised 15 diabetic patients at the age of 35-39 and group three included 6 patients more than 40 years of age. For intrapartum monitoring we used the STAN®S21 system. The results were as follows: in diabetic patients at the age of 30-43, changes of the ST segment of FECG correlated with the higher level of AST and ALT. The higher level of AST correlated with the lower pH value. We did not notice any correlations of AST and ALT with ST segment changes.